Mary Lennox Impoliteness Strategy in movie “The Secret Garden 2020” - Suhenda, Ledise; Marlina, Leni (Universitas Negeri Padang, 2024)
This study was motivated by the phenomenon of rude and cold speech patterns carried out by the main character of the children's story in the film The Secret Garden 2020. This study aims to analyse the types and triggers of Impoliteness Strategies carried out by the main character. In children's stories, there tend to be main characters who are friendly and kind so that they can be examples for their readers. However, unlike the story from the novel